Criminology and moral philosophy empirical methods and the study of values - Jacobs, Jonathan A. 1955- (Routledge, 2022)
"This book offers an introduction to the philosophical issues of criminal justice ethics in a way suitable for students of criminology and criminal justice. It links philosophical concepts with empirical research in criminology and introduces criminal justice ethics, in the context of political and legal order"--
Keywords: Ethik; Kriminologie; Criminal justice, Administration of / Moral and ethical aspects